Les politiques straight du préservatif : VIH, pornographie et technologies du genre - Kira Ribeiro (Genre, Sexualité et Société)
Bisexual and « shemale » porn productions feature specific uses of condoms that give us an insight into HIV politics and sexual politics within the pornographic industry. In some of these productions, intercourse between non-trans men and women is performed without condoms whereas, in the same scene and with the same performers, intercourse between men or involving a trans woman is performed with a condom. Through the analysis of several videos, this article wish to examine what underlies those specific uses of condoms. It aims to understand how those particular prevention policies code for a division of sexuality, gender and sex following a dividing line - real or imaginary but yet signified - between normal and pathological, seronegativity and seropositivity, straightness and queerness.